Inhibition of 5-Lipoxygenase Pathway Attenuates Acute Liver Failure by Inhibiting Macrophage Activation - Lu Li; Yi-Rong Liu; Shan Gao; Jun-Feng Li; Shan-Shan Li; Dan-Dan Zhang; Shuang Liu; Li Bai; Su-Jun Zheng; Zhong-Ping Duan; Min Qi; Yu Chen (Journal of Immunology Research)
This study aimed to investigate the role of 5-lipoxygenase (5-LO) in acute liver failure (ALF) and changes in macrophage activation by blocking it. ALF was induced in rats by administration of D-galactosamine (D-GalN)/lipopolysaccharide (LPS). Rats were injected intraperitoneally with AA-861 (a specific 5-LO inhibitor), 24 hr before D-GalN/LPS administration. After D-GalN/LPS injection, the liver tissue was collected for assessment of histology, macrophage microstructure, macrophage counts, 5-LO mRNA formation, protein expression, and concentration of leukotrienes. Serum was collected for detecting alanine aminotransferase (ALT), aspartate transaminase (AST), total bilirubin (Tbil), and tumor necrosis factor- (TNF-)α. Twenty-four hours after injection, compared with controls, ALF rats were characterized by widespread hepatocyte necrosis and elevated ALT, AST, and Tbil, and 5-LO protein expression reached a peak. Liver leukotriene B4 was also significantly elevated. However, 5-LO mRNA reached a peak 8 hr after D-GalN/LPS injection. Simultaneously, the microstructure of macrophages was changed most significantly and macrophages counts were increased significantly. Moreover, serum TNF-α was also elevated. By contrast, AA-861 pretreatment significantly decreased liver necrosis as well as all of the parameters compared with the rats without pretreatment. Macrophages, via the 5-LO pathway, play a critical role in ALF, and 5-LO inhibitor significantly alleviates ALF, possibly related to macrophage inhibition.